2021
DOI: 10.1111/1750-3841.15894
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and antioxidant property of enzymatic‐transesterification derivatives of (−)‐epigallocatechin‐3‐O‐gallate and vinyl laurate

Abstract: (−)‐Epigallocatechin‐3‐O‐gallate(EGCG) was enzymatically modified to enhance the lipophilicity and the antioxidant property. The determination of optimal reaction conditions are as follows: Lipase DF “Amano” 15 and acetone were used as catalyst and solvent, respectively. Equal molar of EGCG and vinyl laurate (1:1); lipase addition of 6.0% (w/w of total substrates); reaction temperature of 50°C and reaction time of 96 h, which obtained the conversion rate of EGCG at 80.1%. The structure of EGCG lauroyl derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Many studies have reported that increasing the concentration of the acyl donor facilitated the reaction, generating a higher quantity of acylated derivatives. 24,25 As shown in Fig. 2A 1 –2D 1 , TX conversion reached more than 90% for all the ester derivatives.…”
Section: Resultsmentioning
confidence: 68%
“…Many studies have reported that increasing the concentration of the acyl donor facilitated the reaction, generating a higher quantity of acylated derivatives. 24,25 As shown in Fig. 2A 1 –2D 1 , TX conversion reached more than 90% for all the ester derivatives.…”
Section: Resultsmentioning
confidence: 68%
“…The esterification of EGCG could theoretically diminish its antioxidant activity by reducing the number of phenolic hydroxyl groups available for hydrogen donation. It was observed that the scavenging abilities for DPPH free radicals, ABTS + free radicals, and hydroxyl free radicals of EGCG-laurate decreased compared with those of EGCG [40]. Meanwhile, the antioxidant capacity of EGCG-laurate gradually diminished with an increase in the number of substituents.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…The prevalent use of vinyl ester as an acyl donor in enzymatic esterification can be attributed to the facile conversion of vinyl alcohol, generated during the reaction, to acetaldehyde. This allows for the easy elimination of acetaldehyde from the reaction system, thereby shifting the equilibrium toward product formation [40,43]. Additionally, the carbon chain length of the acyl donor significantly influences the synthesis of EGCG esterification products.…”
Section: Enzymatic Modificationsmentioning
confidence: 99%
“…Polyphenols were esterified by maleic anhydride via an attack on the acyl‐carbon center of the anhydride by hydroxyls, disrupting the catechol or pyrogallol structure, thus suppressing o ‐quinone formation (Garcia et al., 2018). For nonester catechins, esterification mainly takes place at C3 site, and for ester catechins, it occurs at hydroxyl groups of B and D rings (Jiang et al., 2021). Palmitoyl chloride was found to be incorporated in the C4 position of B ring, which disrupted o ‐triphenol structures of epigallocatechin gallate (EGCG) (Liu & Yan, 2019).…”
Section: Intervention Strategies For O‐quinone and O‐quinone‐induced ...mentioning
confidence: 99%
“…Enzymatic modification, especially lipases, is preferred in food application due to its mild reaction conditions, specificity as well as selectivity, whereas the use of chemical reagents has disadvantages, such as solvent residues, environmental pollution, and harsh process parameters (Marathe et al., 2022). The conversion yield of EGCG under the catalysis of Lipase DF “Amano” 15 in acetone reached 80.1% (Jiang et al., 2021). An immobilized lipase Novozym 435 was applied to esterify catechin with a maximum conversion rate of 60.36% (Zhou, Tian, et al., 2021).…”
Section: Intervention Strategies For O‐quinone and O‐quinone‐induced ...mentioning
confidence: 99%